Charge history of CO2 in Lishui sag, East China Sea basin: Evidence from quantitative Raman analysis of CO2-bearing fluid inclusions. (December 2018) - Huang, Yahao; Tarantola, Alexandre; Wang, Wenjing; Caumon, Marie-Camille; Pironon, Jacques; Lu, Wanjun; Yan, Detian; Zhuang, Xingguo
Abstract: The accumulation of carbon dioxide in natural gas reservoirs is common, and CO2 gas fields have been widely discovered in the world. In the last decades, three CO2 pools were discovered in Lishui sag, East China Sea Basin. Geochemical proxies indicate that CO2 in these gas reservoirs is dominated by mantle-source volcano degassing. Although three volcanic events occurred in the formation of these reservoirs, the CO2 charging period is not clear. In this study, pure CO2, CO2 -rich and H2 O-rich fluid inclusions were found in healed micro-fractures and overgrowth zones of quartz in the reservoir of Lishui sag. The composition and density of two H2 O-rich inclusions, two CO2 -rich inclusions and twenty-three pure CO2 inclusions were determined by Raman quantitative analysis. The burial depth of CO2 fluid inclusion assemblages (FIA) can be determined by the trapping pressure constrained from Raman quantitative analysis and thermodynamic models. The combination of C-He isotope analyses, PT entrapment conditions of CO2 -bearing inclusions, feature of fault activity and simulation of burial history permits to assign periods of CO2 fluid activity. The low-density (∼0.15 g cm −3 ) CO2 gas inclusions recorded an early-period of CO2 activity eruption to be related with the Late-Paleocene volcanic event. The mid-density (∼0.45 g cm −3 ) and high-density (∼0.75 g cm −3 ) CO2 inclusions were assigned to the Miocene volcanic event and to a later CO2 charging event during Pliocene. Highlights: C-He isotopic results show CO2 is dominated by mantle-derived and contains partial admixtures of curst-derived CO2 gas. Petrography, microthermometry and cathodoluminescence indicate the characteristics of CO2 -bearing inclusions. PVTX properties of pure CO2, CO2 -rich and water-rich fluid inclusions were determined by Raman quantitative analysis. Analysis of multiple CO2 charging time in LS-A, well B and well C based on burial histories modeling.